Inhibitors of acetylcholinesterase and butyrylcholinesterase meet immunity - Pohanka, Miroslav (International journal of molecular sciences, 2014)
Acetylcholinesterase (AChE) inhibitors are widely used for the symptomatic treatment of Alzheimer's disease and other dementias. More recent use is for myasthenia gravis. Many of these inhibitors interact with the second known cholinesterase, butyrylcholinesterase (BChE). Further, evidence shows that acetylcholine plays a role in suppression of cytokine release through a "cholinergic anti-inflammatory pathway" which raises questions about the role of these inhibitors in the immune system. This review covers research and discussion of the role of the inhibitors in modulating the immune response using as examples the commonly available drugs, donepezil, galantamine, huperzine, neostigmine and pyridostigmine. Major attention is given to the cholinergic anti-inflammatory pathway, a well-described link between the central nervous system and terminal effector cells in the immune system.
Keywords: acetylcholinesterasa; imunitní systém; Immunity; Cholinesterase Inhibitors; Immune System; imunita; butyrylcholinesterasa; lidé; Animals; Acetylcholinesterase; cholinesterasové inhibitory; Humans; Butyrylcholinesterase; zvířata